Judges under corruption stress: Lessons from leaked files about corruption in Slovakia - Mazur, Jan (Oñati Socio-Legal Series, 2025)
Judicial corruption represents a critical issue for proper functioning of the rule of law and democracy. I explore the topic of judicial corruption and the role judges and lawyers may play in it in Slovakia. We are accustomed to think of judges under stress from political actors or for ideological reasons, although the Slovak case highlights that pressure may also come from rather banal greed-motivated corruption. The paper compares assumptions about judicial corruption, based on in-depth interviews with judges and lawyers (i. e. "how the judges and lawyers believe the judicial corruption works"), and revelations from the leaks of private communications of a prominent Slovak criminal with multiple judges and lawyers (so-called "Threema" scandal, 2019-2021), which caused an upheaval among the politicians and judiciary in Slovakia (i. e. "how the judicial corruption actually works" as based on investigative journalism and published criminal investigations). The leaks led to dozens of criminal investigations of public servants, politicians, businessmen, judges, or lawyers with over 40 of these investigations concluded with a lawful verdict, which provide credence to the leaks. Both from interviews and leaks, judicial corruption in Slovakia appears to have been available to parties willing to access judges through trust brokers, or "fixers", typically either lawyers, or "entrepreneurs". The nature of judicial corruption was thus be twofold; (i) low-stake, relying on social capital of judges, lawyers, and "fixers", established through common socialization and interests; (ii) relying on cash payments facilitated by specific trust brokers - "fixers", including payments through virtual trusts or secondary trusted service providers. Fixers were not only supposed to influence procedural and meritorious decisions on behalf of their "clients" but also in their own interest in self-initiated legal cases on certain familiar courts and thereby enriching themselves. The paper provides details of suspected corrupt practices, including mechanisms of paying bribes, through comparing interviewees’ perception of judicial corruption and the nature of judicial corruption as based on the leaks covering instances of corrupt practices.